PERTIMBANGAN-PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA PIDANA - Artji Judiolrs Lattan (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2014)
The judge is a state judicial officer authorized by law to prosecute a case that confronted him. In examining and deciding a case, the judge does not just cut but are based on certain considerations. Considerations the judge in deciding the case based on a consideration of the facts of criminal acts, the juridical facts, errors criminal, motive and purpose of committing a crime, the attitude and actions of the perpetrator after committing a crime, the effect of a criminal offense against the victim or the victim's family and the public's view criminal offenses committed. Constraints faced by judges in deciding a criminal case is very thin evidence or lack of evidence that is used both witnesses and evidence, the victim did not provide information in a transparent manner, the prosecutor in presenting the witness not timely and the behavior of the accused during the trial disrespectful, disorderly and do not comply with regulations.